Importance of Physical Activity in Children’s Mental Health - Ikonomi, Edison (Arena-Journal of Physical Activities, 2022)
Introduction: Mental health is an important component of children’s health that affects almost every aspect of their lives. One in five children in the world experiences varying degrees of mental health disorders and the burden of morbidity and mortality from these causes is increasing. For these reasons, the mental health status of children poses a serious concern for health and the health system in general. The purpose of this paper review is to analyze literature of mental health as an important part of a child’s overall health. In fact it has a significant impact on physical health as well as on children’s ability to be successful in school, work and society. Mental health as well as physical health affects the way an individual thinks, feels and acts. Methodology: In order to fulfill this review are using methods of literature analysis, and is made combination and comparison of data from various works of authors varied. To successfully realize this review paper we studied and analyzed the contemporary scientific literature. The methods used are: literature analysis, physical activity mental health and recommendations. Recommendations: all the literature used can be clearly seen the importance of understanding mental health support is essential for addressing the phenomenon and its associated consequences, including, appropriate parental communication, mental health promotion, physical activity as well as specialized psychologist assistance and medical assistance.